Unusual Cytotoxic Steroidal Saponins from the Gorgonian Astrogorgia dumbea - Lu, Ya-Nan; Cui, Ping; Tian, Xiao-Qing; Lou, Li-Guang; Fan, Cheng-Qi (Planta Medica, 2016)
Three steroidal saponins, including astrogorgiosides A (1) and B (2) bearing acetamido-glucose moieties, and astrogorgioside C (3) with a 19-nor and bearing an aromatized B ring steroid aglycone, together with a known major saponin dimorphoside A (4), were obtained from the gorgonian Astrogorgia dumbea collected near Dongshan Island in East China Sea. Structures of these compounds were elucidated by in-depth spectral and chemical methods, including 2D-NMR, HR-ESI-MS spectra, and acidic hydrolysis. For the first time, acetamido-glucose moiety is being reported from a gorgonian. The B-ring aromatized steroid aglycone of compound 3 is also rare in marine natural products. Compounds 1–3 exhibited moderate cytotoxic activity with IC50 values of 26.8–45.6 µM against human tumor cells Bel-7402 and K562.
Keywords: Astrogorgia dumbea; Plexauridae; steroidal saponin; astrogorgiosides A–C; cytotoxic activity